Sequential doping strategy for all-biomass derived N/P co-doped biochar: Unraveling the divergent capture mechanisms in antibiotic removal - Chengyu Li; Qihang Wang; Kunxiang Zhang; Hong He; Lvxin Peng; Jun Mu (Bioresource Technology, 2026)

Within-species phenotypic resistance rather than community turnover tracks antimicrobial usage in Staphylococcus aureus on swine farms - So Hee Park; Jin Gyeong Jeong; Acme Afrin Jahan; Mu Sun Lee; Jeong Yoon Kang; Junsik John Kim; Bo-Youn Moon; Suk-Kyung Lim; Gihan Lee; SeungMuk Yu; Jin-Kyung Hong; Keunje Yoo; et al. (Environmental Pollution, 2026)

Integrating optical remote sensing and airborne gamma for lithological classification using an artificial neural network: A case study in Wuliji, North China - Jun-Ting Qiu; Hong-Xu Mu; Xin-Min Rui; Yun-Han Yang; Liang Qiu (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

A probabilistic prediction model based on uncertainty quantification and interpretable deep learning: Application to runoff prediction in the Yellow River mainstream - Liang Mu; Junxi Chen; Zhiguo Yu; Hong Zhao; Zhibo Yang (Journal of Hydrology, 2026)

Seismic stability of anchored slopes: a comprehensive framework for coupled viscoelastic-rheological effects in anchoring cables and geomaterials - Fa-Qiao Qian; Ya-Hong Deng; Huan-Dong Mu; Fan Liu (Computers and Geotechnics, 2026)

Preparation and evaluation of silicate stabilized FeS nanoslurry for in-situ remediation of hexavalent chromium - Ning-Ning Xing; Hong-Ling Zhang; Pan-Pan Mu; Hui Jiang; Hong-Bin Xu (Chemical Engineering Journal, 2026)

Pyrethrin II impairs mitochondrial potential through ROS and MAPK pathways in HT‑22 cells - Jiaojiao Gao; Xinbi Zhang; Qie Mu; Yurong Liu; Hong Yang; Rui Cao; Xiuwei Wang; Baofeng Yu; Li Zhang; Yaoyao Guo (NeuroToxicology, 2026)

A Systematic Survey and Geoconservation Strategy for Geoheritage Resources in the Guang’an Region, Southwest China - Sibao Zhu; Hong-Xu Mu; Zizheng Wang; Qingwei Song; Minghui Li; Qing Zhou; Jun Liu; Bangguo Zhou; Canhai Jin (Geoheritage, 2026)

Investigation, Evaluation and Geoconservation of the Yardang Landforms in Dahaidao Region, Hami Basin, Xinjiang, NW China - Qing-Wei Song; Hong-Xu Mu; Zhao-Jie Chen; Xu-Dong Song; Xiu-Long Zhang; Ying Dong; Yi-En Xiao (Geoheritage, 2026)

Deciphering the mechanisms underlying regional heterogeneity of high-temperature Daqu through integrated electronic sensory, volatilome, and microbiome analysis - Yu Mu; Hong Zhang; Yingdong Pan; Ziyou Tian; Ying Huang; Liang Yang; Chunlin Zhang; Chi Zhao; Dong Li; Xudong Liu; Li Jiang (International Journal of Food Microbiology, 2026)

Recombinant bovine αs1-casein as an enhanced precursor for sleep-promoting peptides: A structural, peptidomic, and molecular docking study - Long Pan; Lin-Lin Ding; Meng-Jia Song; Xiang-Li Mu; Ai-Mei Liao; Yin-Chen Hou; Ji-Hong Huang; Guang-Hai Yu (Food Bioscience, 2026)

WITHDRAWN: Corrigendum to "H2S-releasing versatile hydrogel dressing with potent antimicrobial, anti-inflammatory, epithelialization and angiogenic capabilities for diabetic wound healing" [Chem. Eng. J. 469 (2023) 143398] - Jiale Chen; Zhixiang Mu; Dongfan Chen; Chen Huang; Ting Jin; Lin Li; Youyun Zeng; Qiang Zhou; Yanmei Zhang; Hongli Mao; Hui Deng; Xinkun Shen; et al. (Chemical Engineering Journal, 2026)

Hepatic Sirt2-PARP1-HMGB1 axis promotes exercise-mediated amelioration of MASH in mice - Shan Li; Wang-Jing Mu; Zi-Ang Zhao; Wan-Qiu Peng; Jie-Ying Zhu; Ruo-Ying Li; Lin-Jing Yan; Yang Li; Hong-Yang Luo; Min Chen; Meng-Ting Yin; Xin Li; et al. (Science China Life Sciences, 2026)

Suicide attempt risk among patients receiving methylphenidate: a retrospective cohort study - Tai-Long Pan; Li-Chi Chen; Ju-Wei Hsu; Ya-Mei Bai; Shih-Jen Tsai; Tzeng-Ji Chen; Mu-Hong Chen (Psychopharmacology, 2026)
Background Methylphenidate may reduce suicide risk among patients with attention-deficit hyperactivity disorder. Several studies have noted that the association between methylphenidate use and suicidality is weakening. Methods Data were collected from Taiwan’s National Health Insurance Research Database to assess the association between methylphenidate exposure and suicide attempt risk across two exposure periods (main analysis: 2001–2002; duplication analysis: 2004–2005). We compared suicide attempt risk between patients who initiated methylphenidate treatment and those with no recorded psychiatric treatment or methylphenidate exposure during the same period. Results In both the main and duplication analyses, patients receiving methylphenidate exhibited a higher subsequent risk of suicide attempts than unexposed individuals. A duration–response pattern was observed in both cohorts: the hazard ratio of suicide attempts declined with longer cumulative methylphenidate use, from 1.60/1.84 for < 30 days to 1.45/1.65 for ≥ 180 days. Because hazard ratios were closely aligned across 2001–2002 and 2004–2005, the association of methylphenidate with reduced suicide attempt risk did not appear to decrease over time. Discussion Longer use of methylphenidate was associated with a lower risk of subsequent suicide attempts among patients in Taiwan receiving methylphenidate. The beneficial effect of methylphenidate on suicide risk remained consistent over time.

A label-free fluorescent/electrochemical dual-mode zinc complex biosensor for highly selective and sensitive detection of tetracycline - Zhi-Lin Mu; Zeyu Zhu; Jiale Cheng; Xingyu Zhan; Chen He; Zhongyan Chen; Hong-Ping Xiao; Jing-Yuan Ge (Analytica Chimica Acta, 2026)

Short-term and lagged effects of ambient air pollution on emergency visits for cardiovascular diseases modified by meteorological factors - Hong Mu; Yufeng Shi; Jiexin Liu; Zhicheng Hu; Xia Wang; Yue Wang; Bin Xu; Rongshan Wu; Jian Xu (International Journal of Hygiene and Environmental Health, 2026)

Unveiling the dynamic characteristics of Rosa roxburghii Tratt wine: A multi-omics and molecular docking study on commercial Saccharomyces cerevisiae and indigenous Hanseniaspora uvarum L31 during fermentation - Dong Li; Xiaoqin Zhang; Yu Mu; Lilan Chen; Huan Guo; Wenyue Yu; Guofang Xie; Hong Gao (Food Chemistry, 2026)

Zinc-reinforced sandwich-structured nano-magnesium oxide composite collagen barrier membrane for promoting bone regeneration - Hong Du; Shasha Lei; Jianhui Wu; Yiruo He; Lun Yuan; Liming Ge; Changdao Mu; Zhilang Xu; Defu Li (Chemical Engineering Journal, 2026)

From traditional to collaborative governance: enhancing disaster resilience under extreme weather in Sichuan Province, China - Qiaoqiao Gui; Hong Wang; Jiahua Mu (Natural Hazards, 2026)

Exposure to second-generation flame retardants and risk of metabolic diseases: a systematic review and meta-analysis - Li Shi; Wei Du; Xi-Yuan Peng; Juan Miao; Wei Li; Attiq Ur-Rehman; Meng-Wei Ge; Lu-Ting Shen; Rui Feng; Kang Zhong; Zhi-Ren Mu; Hong-Lin Chen (Archives of Toxicology, 2026)

Shorter to be effective: subanesthetic-dose ketamine infusion reduces the global and regional path length of brain functional connectivity in patients with treatment-resistant depression and suicidal ideation - Wei-Chen Lin; Li-Kai Cheng; Tung-Ping Su; Li-Fen Chen; Pei-Chi Tu; Cheng-Ta Li; Ya-Mei Bai; Shih-Jen Tsai; Mu-Hong Chen (Psychopharmacology, 2026)

Analysis of the morphological structure and metabolic characteristics of Moniezia in sheep - Qian Mu; Wan-Ling Yao; Bao-Shan Wang; Wen-Zhu Chai; Fu-Hua Liu; Zhen Huang; Yong-Cheng Meng; Jing Pan; Xi-Ping Fan; Wan-Hong He; Wang-Dong Zhang (Veterinary Parasitology, 2026)

The Complete Mitochondrial Genome of a Newly Recorded Chinese Species of Diglyphus sabulosus (Hymenoptera: Eulophidae) and Insights into Its Phylogenetic Position - Lu-Chao Fang; Zhi-Qiang Ge; Ou-Yan Xi; Ze-Lu Mu; Hong-Ying Hu (Biochemical Genetics, 2026)

AI-driven discovery of natural product-derived FAK1 inhibitors for idiopathic pulmonary fibrosis - Xing-Yi Chen; Mei-Hong Lu; Bin Li; Ya Zhou; Li Liu; Hao Yang; Qiu-Yu Wang; Lin Chang; Yu-Lan Zhao; Dong-Mei Wang; Bin Li; Ben-Rong Mu (Molecular Diversity, 2026)

A novel antioxidant peptide DD12 (DWPDARGIWHND) derived from dry cured ham alleviates H2O2-induced oxidative damage via the Keap1-Nrf2-ARE pathway - Ying-dao Nan; Si-qi Chen; Guan-hao Li; Ting-yu Li; Bai-de Mu; Juan Wang; Jian Feng; Hong-mei Li; Chun-xiang Piao (Food Research International, 2026)

Study on the mechanism of mixed biochar enhancing methane production in anaerobic digestion of corn straw - Huilin Zhang; Siyu Zhang; Pujie Wei; Xinyue Zhao; Hong Chang; Zeyan Mu; Xu Zhang; Wei Liu; Xudan Liu; Xiaohong Su; Xin Wang (Biocatalysis and Agricultural Biotechnology, 2026)

Targeting ACSL4: A potential strategy to alleviate deoxynivalenol-mediated intestinal ferroptosis, oxidative stress, and immunosuppression in Channa argus - Yi-Ran Zhao; Tong-Hao Wang; Ze-Xin Zhao; Xiao-Tian Niu; Hong-Ming Lv; Yan-Bing Li; Yang Cao; Mu-Yang Li (Aquaculture, 2026)

Research progress in atmospheric haze chemistry: Formation mechanism of air pollution complex and control technologies - Qingxin Ma; Peng Zhang; Tianzeng Chen; Hao Li; Yonghong Wang; Jun Liu; Pengfei Liu; Yujing Mu; Jingjing Liu; Zhi Liu; Guangyan Xu; Yulong Shan; et al. (Journal of Environmental Sciences, 2026)

Corrigendum to “Identification and functional characterization of cGAS and cGAS-like in snakehead Channa argus” [Fish Shellfish Immunol. 165 (2025) 110566] - Hong Qing Zhang; Long Wei Cai; Yu Hang Deng; Meng Xin Yan; Peng Fei Mu; Bo Li; Lan Hao Liu; P. Nie (Fish & Shellfish Immunology, 2026)

Quinone structure regulates sulfide-driven reactive oxygen species generation for aquatic pollutant degradation - Han-Qing Zhao; Ruihan Yu; Jiayi Liu; Hong Cheng; Aqiang Ding; Daijun Zhang; Yang Mu; Peili Lu (Water Research, 2026)

Rice SINA E3 ligases dichotomously control ERECTA1 ubiquitination and stability to regulate panicle morphogenesis and grain yield - Zi-Qi Lu; Tao Guo; Ying-Jie Cao; Jun-Xiang Shan; Wang-Wei Ye; Nai-Qian Dong; Yi Kan; Yi-Bing Yang; Shuang-Qin Guo; Jie-Jie Lei; Xiao-Rui Mu; Ji-Fu Zhou; et al. (Molecular Plant, 2026)

Spatial characterization and health risk evaluation of residual phenol five years after a river pollution incident - Tingting Liu; Fengjing Song; Yiming Sun; Zhen Ding; Hao Zheng; Shixuan Hao; Hong Xu; Yan Liu; Chao Wang; Xiaomin Xie; Mu Zhu; Peixuan Shen; et al. (Journal of Hazardous Materials, 2026)

Organ-specific toxicity of Maillard-derived 2-furfural and 5-hydroxymethylfurfural: Quantitative evidence from zebrafish - Xiangxin Wang; Qingxue Chen; Shubo Luo; Dongying Cui; Sinan Mu; Jufang Li; Qinggang Xie; Bailiang Li; Hong You (Food Research International, 2026)

Structural modulation of casein peptide-hydroxytyrosol self-assembled nanocomplexes: Enhanced gastrointestinal stability and in vitro antioxidant activity - Si-Yi Han; Hong-Fu Zhao; Wen-Qi Liang; Ying-Hua Zhang; Zhi-Shen Mu (Food Research International, 2026)

Microscopic probing into plasmodesmata (PD) and PD-derived intercellular gateways (PdIGs): Beyond morphology - Ming-fang Lv; Wei-na Shang; Yuan-xing Dai; Jun-ying Li; Yi Li; Shuai Fu; Jian Hong; Li Xie; Heng-Mu Zhang (Protoplasma, 2026)

Excavation instability with end restraint effect under high stress: insights from True-Triaxial simulation experiments - Ting Zhang; Si-Qiao Wang; Shi-Hong Wu; Mu-Qing Su; Jian-Zhi Zhang; Yong Niu (Bulletin of Engineering Geology and the Environment, 2026)

Anti-diabetic quinolone alkaloids from the fruits of Tetradium ruticarpum - Chun-Lin Zhao; Kai-Wen Kang; Zhi-Cheng Su; Hong-Yan Mu; Hui-Shan Guo; Hui-Zhen Chen; Ya-Ting Chen; Jing-Wei Jin; Ju-Cai Xu; Hong-Guang Li; Li-She Gan (Phytochemistry Letters, 2025)

Prediction and analysis of polyvinylidene fluoride membrane pyrolysis reaction based on machine learning framework - Hong Su; Yadong Ge; Xiaohua Wang; Lan Mu; Beibei Yan; Guanyi Chen (Journal of Environmental Chemical Engineering, 2025)

Biodegradation of unpretreated polypropylene microplastic and agricultural polypropylene film by a bacterium isolated from an oil reservoir - Sheng Jin Li; Yun Yang Wan; Zhe Ke Zhong; Ying Jia Zhu; Hong Mei Mu; Sheng Bao Shi (Journal of Environmental Chemical Engineering, 2025)

Predicting and interpreting nitrogen removal performance and functional microbial abundance of single-stage partial nitrification and anammox system using machine learning methods - Xiulin Mu; Fangxu Jia; Shengming Qiu; Yiran Li; Ning Mei; Xingcheng Zhao; Baohong Han; Xiangyu Han; Jingjing Zhang; Hong Yao (Bioresource Technology, 2025)

Golgi-associated TRAF6 as a regulator of protein convertase FURIN for insulin receptor precursor processing - Minjun Liu; Kun Zhou; Yang Sheng; Wen Zhang; Qiaoli Chen; Ziyue Chen; Xinyu Yang; Yuxin Jin; Fangtong Liu; Yinqiu Mu; Shu Su; Weikuan Feng; et al. (Science China Life Sciences, 2025)

The critical role of mitophagy in cell senescence-mediated pulmonary fibrosis and potential therapeutic strategies - Xing-Yi Chen; Dong-Mei Wang; Ya Zhou; Li Liu; Tao Zhu; Zhao Ran; Mei-Hong Lu; Ben-Rong Mu (Molecular Biology Reports, 2025)

Rapid formation of acetaldehyde and its influence on ozone formation in a petrochemical industrialized region - Can Cui; Yujiao Zhu; Xiaoyu Yan; Xin Zhang; Min Zhao; Jiangshan Mu; Xuelian Zhong; Jinghao Tang; Yanqiu Nie; Cong An; Wanghui Chu; Yue Sun; et al. (Journal of Environmental Sciences, 2025)

Effect of desalination-related pH shift on whey protein structure and digestion: Insights from spectroscopy, molecular dynamics simulation, and peptidomics - Meng-Qi Liu; Yun Chen; Hong-Fu Zhao; Ying-Chao Qiu; Ying-Hua Zhang; Zhi-Shen Mu (Food Chemistry, 2025)

Regulation of peptide hydrophobicity by self-assembly of casein peptides with ferulic acid to potentially reduce peptide bitterness and improve in vitro digestive activity - Si-Yi Han; Hong-Fu Zhao; Bo-Kang Yu; Ying-Hua Zhang; Zhi-Shen Mu (Food Chemistry, 2025)

Investigating the variations in microbiome and volatilome characteristics of sauce-flavor Muqu across different grades and production rounds - Yu Mu; Linpei Liu; Junjun He; Hong Zhang; Shirui Yu; Zhiyu Zhu; Ying Huang; Mingyue Mou; Chunlin Zhang (Food Chemistry, 2025)

Optimizing biogas residue composting: Impact of biochar and zeolite co-loaded with lignocellulose-degrading microbial agents on degradation, humification, and microbial ecology - Hong Chang; Ruian Lin; Xiaohong Su; Xinrui Xu; Wei Liu; Yilin Zhang; Zeyan Mu; Xin Wang; Anina James; Junting Pan (Journal of Environmental Chemical Engineering, 2025)

Integrated machine learning model for prediction of nutrients contents and maturity in rural organic solid wastes aerobic composting - Hao Peng; Lan Mu; Yingjin Song; Hong Su; Yadong Ge; Zhanjun Cheng; Rundong Li; Guanyi Chen (Journal of Environmental Chemical Engineering, 2025)

Identification and functional characterization of cGAS and cGAS-like in snakehead Channa argus - Hong Qing Zhang; Long Wei Cai; Yu Hang Deng; Meng Xin Yan; Peng Fei Mu; Bo Li; Lan Hao Liu; P. Nie (Fish & Shellfish Immunology, 2025)

Cellulose-sponge hierarchical architecture-based ultra-high linearity flexible pressure sensor for magnitude and acting point detection - Shaowen Mu; Jianhong Hao; Yuqing Xia; Chenyang Hong; Jingxi Wang; Xincheng Tang; Ziqiang Wang; Xiaowen Zhu; Cancan Lv; Yunong Zhao; Siliang Wang; Xiaohui Guo (Chemical Engineering Journal, 2025)

Phase-interfacial engineering of 2H@1 T-WS2-x cocatalyst to accelerate H2 production on SnS2 - Jianchun Wang; Nan Mu; Ruixin Xu; Xin Hong; Yanyu Liu; Wei Zhou (Chemical Engineering Journal, 2025)

The potential of energy-divergent ultrasound, slightly acidic electrolyzed water and peracetic acid in sweet potato preservation to control Rhizopus stolonifer - Guang-Chen Liu; Hong-Nan Sun; Miao Zhang; Tai-Hua Mu (Food Control, 2025)

Comparative analysis of rural organic waste treatment: greenhouse gas emissions, economics, and energy flow - Hao Peng; Lan Mu; Yingjin Song; Dan Zeng; Hong Su; Zhanjun Cheng; Rundong Li; Guanyi Chen (Biomass and Bioenergy, 2025)

Using Interactive Multi-Media Panorama Virtual Reality to Balance Heritage Science, Education and Conservation At Zhoukoudian, Fangshan UNESCO Global Geopark - Jun-Ting Qiu; Tong-Yu Zhang; Lixian Tian; Xin-Min Rui; Hong-Xu Mu; Liang Qiu; Long-Xin Xu (Geoheritage, 2025)

County-level coordination between urbanization and ecological change in dryland urban agglomerations: A quantitative approach based on remote sensing - Chunqiang Li; Shanchuan Guo; Zilong Xia; Xiaoquan Pan; Haowei Mu; Hong Fang; Pengfei Tang; Peijun Du (Journal of Geographical Sciences, 2025)

CAFM: a freeware for geochemical data processing and concentration–area fractal modeling and its application for identifying uranium anomalies of different genesis - Jun-Ting Qiu; Jiang-Kun Li; Hong-Xu Mu; Xin-Min Rui; Yun-Han Yang; Liang Qiu (Applied Geochemistry, 2025)

Environmental occurrence, human exposure routes, toxicity, and risk assessments of medium-chain chlorinated paraffins (MCCPs): a comprehensive review - Zhi-Hong Yu; Ying-Wen Mu; Yan-Chao Du; Tao Zeng (Archives of Toxicology, 2025)

Accelerated C-F bond cleavage on sulfur vacancy-contained CoS2/MoS2 electrode featuring rich H* - Zhenglin Chen; Guangzhen Liu; Yuqi Hong; Lixia Yang; Xuefei Li; Hui Xiao; Yi Mu; Yue Li; Jianping Zou; Shenglian Luo (Journal of Hazardous Materials, 2025)

Bone marrow microenvironment-targeted yolk-shell nanoparticle enhances acute myeloid leukemia chemotherapy by preventing endothelial cell/ECM-mediated adhesion - Shiyi Hong; Pei Peng; Yutian Huang; Siying Cai; Cao Yao; Tongtong Huang; Yulu Ying; Wei Li; Yang Xiong; Mancang Gu; Guilin Cheng; Chaofeng Mu (Chemical Engineering Journal, 2025)

Exploring Morphological Indicators for Ramet Age Discrimination of Fargesia nitida Based on Growth Patterns - Xiu-xin Mu; Kai-ming Lei; Hong-ou Sun; Pei-gang Kuang; Yue Zhang; Guo-lan Wang; Tao Zeng (Journal of Plant Growth Regulation, 2025)

Nucleotide loss caused by alkaline phosphatase renaturation during infant formula production - Xiangxin Wang; Zhewen Wei; Sinan Mu; Xueyin Qu; Jianqiao Li; Hong You; Yang Xie; Shilong Jiang; Jianguo Sun; Bailiang Li; Qinggang Xie (Food Chemistry, 2025)

Coexisting plants restored in karst desertification areas cope with drought by changing water uptake patterns and improving water use efficiency - Lulu Cai; Kangning Xiong; Yuan Li; Ziqi Liu; Dayun Zhu; Hong Liang; Yating Mu; Yi Chen (Journal of Hydrology, 2025)

Targeting IGF1 to alleviate obesity through regulating energy expenditure and fat deposition - Ping Rong; Yinqiu Mu; Meiqin Wang; Liang Chen; Fangtong Liu; Yuxin Jin; Weikuan Feng; Kun Zhou; Hui Liang; Hong-Yu Wang; Shuai Chen (Science China Life Sciences, 2025)

Unbiased Estimation of the Maximum Wave Height-to-Significant Wave Height Ratio Using Wave Monitoring Data - Hong Yeon Cho; Gi Seop Lee; Weon-Mu Jeong; Kyong Ho Ryu; Yeon S. Chang (Ocean Science Journal, 2025)

Role of myostatin promoter mutations in growth and molting regulation of Macrobrachium rosenbergii - Qiyao Su; Jie Wei; Yakun Wang; Bai Liufu; Huarong Li; Zhuang Mai; Kunhao Hong; Qiaoyan Zhou; Tianhui Jiao; Xidong Mu; Lingyun Yu (Frontiers in Marine Science, 2025)
Myostatin ( Mstn ), a negative regulatory factor in myocytes, has garnered significant attention. This study focused on the Mstn gene and its 24-base-pair mutant in the promoter region of the giant freshwater prawn ( Macrobrachium rosenbergii ), aiming to investigate the regulatory roles of Mstn and its mutant in M. rosenbergii . The research provides theoretical insights into the functional mechanisms of Mstn in crustaceans. Spatiotemporal expression patterns revealed Mstn presence throughout embryonic development and in various body tissues, with peak expression during the gastrula stage and in the hepatopancreas. During the molting cycle, Mstn expression levels decreased in the order of post-molt (A phase), pre-molt (D3 phase), and molting (E phase). Knockdown experiments targeting two genotypes within the Mstn promoter region significantly reduced growth rates and extended molting cycles compared to control group. Further trials on the F2 generation confirmed these findings, highlighting that promoter knockdown influenced the expression of three molting-related genes and slowed the growth rate of M. rosenbergii . This study clarifies the functional role of Mstn in crustacean growth and molting, providing a foundation for understanding its regulatory mechanisms and offering potential applications in aquaculture.

Unrecognized role of photosynthetic bacteria in aquaculture water purification: Producing singlet oxygen to degrade residual pharmaceuticals - Mu-Cen Yao; Qi Huang; Hong-Xuan Xie; Xin Zhang; Guo-Ping Sheng (Water Research, 2025)

Preparation and characterization of microcapsules for tuna oil by maillard reaction products of whey protein isolate and Arabic gum via complex coacervation - Kun-Long Wang; Bo-Kang Yu; Hong-Fu Zhao; Ye-Xuan Liu; Chun-Ying Wu; Ying-Hua Zhang; Zhi-Shen Mu (Food Chemistry, 2025)

Rational application of QoIs fungicides to achieve a rice-fungi-fish interaction balance within paddy ecosystems - Hong Li; Xueqing Wang; Beixing Li; Jin Lin; Feng Liu; Wei Mu (Environmental Pollution, 2025)

A double cross-linked film based on carboxymethyl chitosan binding with L-cysteine/ oxidized konjac glucomannan with slow-release of nisin for food preservation - Zihao Zhang; Lu Mu; Jinlong Li; Haixin Zhao; Hong-Man Hou; Gong-liang Zhang; Hongshun Hao; Jingran Bi (Food Chemistry, 2025)

Parkinson's Disease and the Microbiota-Gut-Brain Axis: Metabolites, Mechanisms, and Innovative Therapeutic Strategies Targeting the Gut Microbiota - Zhao Ran; Ben-Rong Mu; Dong-Mei Wang; Xin-Huang; Quan-Hong Ma; Mei-Hong Lu (Molecular Neurobiology, 2025)

A novel and flexible way to derive water quality criteria for copper - Yang Li; Di Mu; Hong-Qing Wu; Xian-Hua Liu; Jun Sun; Zhi-Yong Ji (Science of The Total Environment, 2025)

Potential effects of pH changes in the micro-environment during desalination on infant powder: The perspective of pH shift affecting whey protein molecular structure and function - Meng-Qi Liu; Wen-Xiu Zhi; Hong-Fu Zhao; Ying-Chao Qiu; Kun-Long Wang; Ying-Hua Zhang; Zhi-Shen Mu (Food Hydrocolloids, 2025)

Geosites Associated with Paleovolcanic Landscapes and Paleontology in Hoboksar Mongol Autonomous County, Xinjiang Uygur Autonomous Region, NW China - Hong-Xu Mu; Qing-Wei Song; Jun-Ting Qiu; Long-Xin Xu; Xin-Min Rui (Geoheritage, 2025)

Enhancing simulations of biomass and nitrous oxide emissions in vineyard, orchard, and vegetable cropping systems - Mu Hong; Yao Zhang; Lidong Li; Keith Paustian (Agricultural Systems, 2025)

Associations between co-exposure to multiple heavy metals and age-related macular degeneration: A cross-sectional study - Mu-hong Wei; Ju-xiao Li; Jing Mi; Qing Wang; Feng Xu; Che Xu (Journal of Trace Elements in Medicine and Biology, 2025)

A pH-responsive fluorescent film with the smartphone-assistance for real-time and visual detection of food freshness - Lu Mu; Huihui Wang; Zihao Zhang; Hong-Man Hou; Gong-Liang Zhang; Hongshun Hao; Jingran Bi (Food Chemistry, 2025)

Urbanization exacerbates disparities in exposure to air pollution in China - Xiuling Zhao; Weiqi Zhou; Mu Hong; Andreas M. Neophytou (Environmental Research, 2025)

Modeling soil organic matter changes under crop diversification strategies and climate change scenarios in the Brazilian Cerrado - Jorge Luiz Locatelli; Stephen Del Grosso; Rafael Silva Santos; Mu Hong; Ram Gurung; Catherine E. Stewart; Maurício Roberto Cherubin; Cimélio Bayer; Carlos Eduardo Pellegrino Cerri (Agriculture, Ecosystems & Environment, 2025)

Highly selective capture of Ni2+ from complex environments by a sandwich-like layered metal sulfide ion exchanger - Mingdong Zhang; Qisheng Hong; Yuan Aocheng; Yan Zhang; Xiaoying Huang; Meiling Feng; Jingli Mu (Journal of Hazardous Materials, 2025)

Enhanced chemiluminescence by carbon dots for rapid detection of bisphenol A and nitrite - Yujie Xiao; Xiaoqin Long; Xue Zhang; Junjie Mu; Qiuxiong Chen; Yuxian Mai; Ying Li; Hao Xue; Pengyang Song; Xian Yang; Hong Zheng (Food Chemistry, 2025)

Effects of ultrasound with slightly acid electrolytic water on storage of sweet potato: Physiological, nutritional, sensory and microstructural characteristics - Lulu Li; Hong-Nan Sun; Miao Zhang; Tai-Hua Mu (Food Control, 2025)

The performance of a 100 m3 outdoor atmospheric simulation chamber in China - Yangang Ren; Jinhe Wang; Wenya Niu; Yang Jiao; Chenglong Zhang; Ravi Yadav; Yonghong Wang; Junfeng Liu; Chunshan Liu; Yujing Mu; Hong He (Science of The Total Environment, 2024)

Enhancing immune defense against COVID-19: Alveolar delivery of mucosal vaccines - Pei-Huang Wu; Dong-Chun Hong; Chu Xie; Mu-Sheng Zeng; Cong Sun (Science Bulletin, 2024)

Cyanobacterial blooms prediction in China’s large hypereutrophic lakes based on MODIS observations and Bayesian theory - Yichen Du; Huan Zhao; Junsheng Li; Yunchang Mu; Ziyao Yin; Mengqiu Wang; Danfeng Hong; Fangfang Zhang; Shenglei Wang; Bing Zhang (Journal of Hazardous Materials, 2024)

Derivation of marine water quality criteria for copper based on artificial neural network model - Yang Li; Di Mu; Hong-Qing Wu; Xian-Hua Liu; Jun Sun; Zhi-Yong Ji (Environmental Pollution, 2024)

Enhancement and Preservation of Tufa Geosites in the Baishuitai Region, Yunnan Province, Southwest China - Hong-Xu Mu; Qing-Wei Song; Gui-Hua Wu; Long-Xin Xu (Geoheritage, 2024)

Orthogonal photochemistry toward spatial reprogramming of 3D-printed liquid crystal elastomers - Hong Wan; Guancong Chen; Xiaorui Zhou; Hongfeng Mu; Chen Yang; Di Chen; Chujun Ni; Zizheng Fang; Qian Zhao; Tao Xie; Ning Zheng (Chemical Engineering Journal, 2024)

Two glycosyl transferase 2 genes from the gram-positive bacterium Clostridium ventriculi encode (1,3;1,4)-β-D-glucan synthases - Shu-Chieh Chang; Rebecka Karmakar Saldivar; Mu-Rong Kao; Xiaohui Xing; Chun-Hong Yeh; Jiun-Jie Shie; D. Wade Abbott; Philip J. Harris; Yves S.Y. Hsieh (Carbohydrate Polymers, 2024)

The role and mechanism of β-catenin-mediated skeletal muscle satellite cells in osteoporotic fractures by Jian-Pi-Bu-Shen formula - Yanghua Tang; Zhuosong Mu; Dong Pan; Renqi Liu; Shenghu Hong; Zhenfei Xiong (Journal of Molecular Histology, 2024)

Bio-refinery of palm kernel expeller waste into attached microalgal biodiesel, the life cycle analysis of waste biomass-to-energy - Hemamalini Rawindran; Kuan Shiong Khoo; Ratchaprapa Raksasat; Chin Seng Liew; Wai Hong Leong; M. Devendran; Balasubramani Ravindran; Woei-Yenn Tong; Jin Chung Sin; Sze Mun Lam; Mu. Naushad; Jun Wei Lim (Process Safety and Environmental Protection, 2024)

Versatile additive for enhancing the stability of Zn Anode: Pyrrolidine-based ionic liquid - Kailimai Su; Hong Zhang; Yan Wang; Xingyun Zhang; Yongbiao Mu; Zhibin Lu; Ye Han; Shanhong Wan; Junwei Lang (Chemical Engineering Journal, 2024)

Dimeric piperidinoquinoline alkaloids from the seeds of Chimonanthus salicifolius - Zhan-Peng Yu; Yu-Xia Wang; Li-Hong Hong; Ya-Lin Li; Jian-Fei Zhang; Mu Li; Ping Ying; Qiang Zheng; Ling-Yi Kong; Jian-Guang Luo (Phytochemistry Letters, 2024)

Exploring the novel antioxidant peptides in low-salt dry-cured ham: Preparation, purification, identification and molecular docking - Ying-dao Nan; Bai-de Mu; Chang-xin Ge; Si-qi Chen; Ming-xun Cui; Hong-mei Li; Chang-cheng Zhao; Juan Wang; Chun-xiang Piao; Guan-hao Li (Food Chemistry, 2024)

Insights into atmospheric trace gases, aerosols, and transport processes at a high-altitude station (2623 m a.s.l.) in Northeast Asia - Ye Shan; Yujiao Zhu; Yanbi Qi; Yu Yang; Jiangshan Mu; Mingxuan Liu; Hongyong Li; Ji Zhang; Yanqiu Nie; Yuhong Liu; Min Zhao; Xin Zhang; et al. (Atmospheric Environment, 2024)

Experimental study on flow kinematics and pressure characteristics of dam break flow - Hyung Joon Kim; Jong Mu Kim; Jae Hong Kim; Kwang Hyo Jung; Gang Nam Lee (Ocean Engineering, 2024)

A hybrid approach of anaerobic digestion model no. 1 and machine learning to model and optimize continuous anaerobic digestion processes - Yadong Ge; Junyu Tao; Zhi Wang; Lan Mu; Wei Guo; Zhanjun Cheng; Beibei Yan; Yan Shi; Hong Su; Guanyi Chen (Biomass and Bioenergy, 2024)

Exploring the potential in postharvest preservation of sweet potato: 2-methylbutanoic acid, isobutyric acid, perillaldehyde and salicylaldehyde, to control Rhizopus stolonifer - Lulu Li; Hong-Nan Sun; Miao Zhang; Tai-Hua Mu (Postharvest Biology and Technology, 2024)

Glyphosate exposure affected longevity-related pathways and reduced survival in asian honey bees (Apis cerana) - Dong Zhi-Xiang; Li Wan-Li; LI Xi-Jie; Li Jia-Li; Zhang Jun; Zhao Chong-Hui; Huang Qi; Cao Zhe; Chen Yuan; Zhao Hong-Mu; Guo Jun; Tian Wen-Li (Chemosphere, 2024)

Brunonianines A-C, C20-diterpenoid alkaloids with cyano group from Delphinium brunonianum Royle - Qing Li; Zhi-Wei Wang; Mu-Xuan Wang; Hao-Lin Yu; Lei Chen; Zhuoer Cai; Yu Zhang; Min-Min Gu; Yuan-Ling Shao; Hong-Ping Han; Zhi-Xin Liao (Phytochemistry, 2024)

Dynamic responses of multi-story structural systems with separated gravity and lateral resisting systems under seismic action considering connection semi-rigidity effects - He Zhao; Xin-Yu Qian; Xiao-Gang Liu; Hong-Bing Chen; Mu-Xuan Tao (Engineering Structures, 2024)

Ambient atmospheric application and influencing factors of ozone catalytic decomposition materials in a channel test - Shuyang Xie; Zhouming He; Yuzheng Wang; Renzhe Zhang; Jinzhu Ma; Yujing Mu; Junfeng Liu; Hong He (Atmospheric Environment, 2024)

A bibliometric assessment of the science and practice of blue–green space (BGS): hot spots, lacunae, and opportunities - Bo Mu; Ruting Zhao; Yang Liu; Enkai Xu; Yali Zhang; Hong Wei; Guohang Tian (Socio-Ecological Practice Research, 2024)

Enhanced Beta2-band Oscillations Denote Auditory Hallucination in Schizophrenia Patients and a Monkey Model of Psychosis - Shuo Ma; Tianzhen Chen; Wenjun Jia; Jie Liu; Shihan Ding; Puzhe Li; Hong Gan; Dapeng Zhang; Shuxin Shao; Mu-Ming Poo; Min Zhao; Bomin Sun; et al. (Neuroscience Bulletin, 2024)

The Relationships Between Danxia Geoheritages and Regional Tectonics in Southern Sichuan Basin: Implications for the Spatial Distribution of Danxia Landforms in China - Jun-Ting Qiu; Hong-Xu Mu; Xin-Min Rui; Yan-Jie Yang; Pengju Li; Liang Qiu; Chao-Bin Xu (Geoheritage, 2024)

Soil N 2 O emissions from specialty crop systems: A global estimation and meta‐analysis - Lidong Li; Mu Hong; Yao Zhang; Keith Paustian (Global Change Biology, 2024)
Nitrous oxide (N 2 O) exacerbates the greenhouse effect and thus global warming. Agricultural management practices, especially the use of nitrogen (N) fertilizers and irrigation, increase soil N 2 O emissions. As a vital sector of global agriculture, specialty crop systems usually require intensive input and management. However, soil N 2 O emissions from global specialty crop systems have not been comprehensively evaluated. Here, we synthesized 1137 observations from 114 published studies, conducted a meta‐analysis to evaluate the effects of agricultural management and environmental factors on soil N 2 O emissions, and estimated global soil N 2 O emissions from specialty crop systems. The estimated global N 2 O emission from specialty crop soils was 1.5 Tg N 2 O‐N year −1 , ranging from 0.5 to 4.5 Tg N 2 O‐N year −1 . Globally, soil N 2 O emissions exponentially increased with N fertilizer rates. The effect size of N fertilizer on soil N 2 O emissions generally increased with mean annual temperature, mean annual precipitation, and soil organic carbon concentration but decreased with soil pH. Global climate change will further intensify the effect of N fertilizer on soil N 2 O emissions. Drip irrigation, fertigation, and reduced tillage can be used as essential strategies to reduce soil N 2 O emissions and increase crop yields. Deficit irrigation and non‐legume cover crop can reduce soil N 2 O emissions but may also lower crop yields. Biochar may have a relatively limited effect on reducing soil N 2 O emissions but be effective in increasing crop yields. Our study points toward effective management strategies that have substantial potential for reducing N 2 O emissions from global agricultural soils.

Tracing magmatic differentiation of peralkaline granites by using K stable isotopes - Hang Xu; Weiqiang Li; Xiao-Lei Wang; Jun Mu; De-Hong Du; Jiao-Long Zhao; Ding-Yi Xiong (Geochimica et Cosmochimica Acta, 2024)

Transformation of exogenous hexavalent chromium and imidacloprid in soils - Xian’an Yu; Tingting Mu; Tong Zhou; Yujuan Huang; Hong Chen; Changxun Dong; Longhua Wu; Peter Christie (Journal of Soils and Sediments, 2024)

Aeromonas hydrophila causes ferroptotic damage via its secreted effectors targeting splenic macrophages in teleost - Hao Sun; Xiaoyu Ma; Qingqing Liu; Hengyi Hu; Xinyan Wang; Anying Zhang; Kun Yang; Mu Yang; Hong Zhou (Aquaculture, 2024)

Quantifying landscape connectivity gaps between protected area and natural habitat - Haowei Mu; Shanchuan Guo; Xuecao Li; Yuyu Zhou; Yihe Lü; Xiaoping Du; Jianxi Huang; Chaode Ma; Xingang Zhang; Zilong Xia; Hong Fang; Peijun Du (Journal of Cleaner Production, 2024)

Non-radical mediated reduced graphene oxide/polypyrrole catalytic ceramic membrane-PDS system for source control of SMX - Rui Wang; Hong You; Zhipeng Li; Jing Zhao; Mu Li; Jing Zhu; Guoyu Zhang; Xianshi Wang; Haoran Leng; Shaojie Qi; Binghan Xie (Chemical Engineering Journal, 2024)

Targeting mitophagy for neurological disorders treatment: advances in drugs and non-drug approaches - Xiong Yang; Yu Zhang; Jia-xin Luo; Tao Zhu; Zhao Ran; Ben-Rong Mu; Mei-Hong Lu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Lidocaine pretreatment attenuates inflammatory response and protects against sepsis-induced acute lung injury via inhibiting potassium efflux-dependent NLRP3 activation - Kai Su; Xin-Tao Li; Fang-Xiao Hong; Mu Jin; Fu-Shan Xue (Inflammation Research, 2023)

Rapid identification of hazardous heavy metal-containing waste by combining EDXRF with machine learning: Taking zinc smelting waste as an example - Jing Teng; Yao Shi; Zuo-Hua Liu; Hui-Quan Li; Ming-Xing He; Zhi-Hong Li; Chen-Mu Zhang (Resources, Conservation and Recycling, 2023)

Thiocarbonyl fluoride generated in situ from difluorocarbene for cyclization of vicinal X-H substituted amines (X = N, O or S) - Jia-Lu Hu; Mu-Xian Fu; Ji-Chang Xiao; Jin-Hong Lin (Journal of Fluorine Chemistry, 2023)

Vitamin D ameliorates Aeromonas hydrophila-induced iron-dependent oxidative damage of grass carp splenic macrophages by manipulating Nrf2-mediated antioxidant pathway - Hao Sun; Dan Wang; Jingqi Ren; Jiaxi Liu; Zhe Wang; Xinyan Wang; Anying Zhang; Kun Yang; Mu Yang; Hong Zhou (Fish & Shellfish Immunology, 2023)

Revised system for shallow-water design wave estimation on the coast of the Republic of Korea based on numerical model data - Jong-Dai Back; Yeon S. Chang; Kyong Ho Ryu; Hong Yeon Cho; Hyuk Jin Choi; Weon Mu Jeong (Ocean & Coastal Management, 2023)

The molecular basis of heat stress responses in plants - Yi Kan; Xiao-Rui Mu; Jin Gao; Hong-Xuan Lin; Youshun Lin (Molecular Plant, 2023)

Lactic acid bacteria with probiotic characteristics in fermented dairy products reduce cow milk allergy - Zi-Hao Guo; Qi Wang; Jing-Hong Zhao; Yun-Peng Xu; Guang-Qing Mu; Xue-Mei Zhu (Food Bioscience, 2023)

C21 steroids from the roots of Marsdenia tenacissima - Jin-Ling Liu; Hong-Tao Xu; Dan-Dan Mu; Xiao Han; Ting-Ting Du; Yong-li Wang; Xiao-Hui Wei; Gui-Xin Chou (Phytochemistry, 2023)

Maternal exposure to cetylpyridinium chloride impairs oogenesis by causing mitochondria disorder in neonates - Ronglu Liu; Xinyi Mu; Rufei Gao; Yanqing Geng; Yan Zhang; Xuemei Chen; Xin Yin; Hong Wang; Fangfang Li; Junlin He (Environmental Toxicology and Pharmacology, 2023)

Synergistic generation mechanisms of SOA and ozone from the photochemical oxidation of 1,3,5-trimethylbenzene: Influence of precursors ratio, temperature and radiation intensity - Hao Zhang; Hong Li; Yujie Zhang; Xuezhong Wang; Fang Bi; Lingshuo Meng; Yunfeng Li; Lu Zhao; Xin Zhang; Zhijian Peng; Yujing Mu; Wahid Mellouki; et al. (Atmospheric Research, 2023)

Understanding the digestibility of wheat starch- caffeic acid complexes prepared by hot-extrusion 3D printing technology - Xin-Ru Cui; Yu-Sheng Wang; Yan Chen; Hong-Yan Mu; Hai-Hua Chen (Food Hydrocolloids, 2023)

H2S-releasing versatile hydrogel dressing with potent antimicrobial, anti-inflammatory, epithelialization and angiogenic capabilities for diabetic wound healing - Jiale Chen; Zhixiang Mu; Dongfan Chen; Chen Huang; Ting Jin; Lin Li; Youyun Zeng; Qiang Zhou; Yanmei Zhang; Hongli Mao; Hui Deng; Xinkun Shen; et al. (Chemical Engineering Journal, 2023)

Intrageneric Relationship of Datnioides (Lobotiformes) Inferred from the Complete Nuclear Ribosomal DNA Operon - Yuanyuan Wang; Hong Zhou; Yexin Yang; Jinhui Sun; Yi Liu; Chao Liu; Sudong Xia; Xidong Mu (Biochemical Genetics, 2023)

Fungal communities, nutritional, physiological and sensory characteristics of sweet potato under three Chinese representative storages - Lulu Li; Hong-Nan Sun; Miao Zhang; Tai-Hua Mu; Nasir Mehmood Khan; Shujaat Ahmad; Shamil Z. Validov (Postharvest Biology and Technology, 2023)

Eugenilones A−N: sesquiterpenoids from the fruits of Eugenia uniflora - Mu Chen; Run-Qiang Chen; Yuan Guo; Jian-Xin Chen; Qian Jin; Mei-Hong Chen; Bo-Yong Chen; Zheng-Chao Tu; Wen-Cai Ye; Lei Wang (Phytochemistry, 2023)

Mechanistic insights into the migration behavior of cadmium (Cd) in the soil and groundwater systems at a construction site: Experimental and numerical analysis - Da–Mao Xu; Ze–Lin Xu; Zi–Qi Mu; Bai–Hong An; Xiao–Wen Fang; Rong–Bing Fu (Journal of Environmental Chemical Engineering, 2023)

Mechanistic insights into dissolved organic matter-driven protistan and bacterial community dynamics influenced by vegetation restoration - Zhang-mu Jing; Qing-qian Li; Yan-jie Wei; Bin Dong; Peng Yuan; Rui-xia Liu; Hong-jie Gao (Environmental Research, 2023)

Sediment sources and their impacts on a check dam-controlled watershed, Loess Plateau, China - Lu-lu Bai; Peng Shi; Wen Wang; Zhan-bin Li; Kun-xia Yu; Peng Li; Ling-zhou Cui; Rong-jian Shen; Mu-hong Guan; Xin-chun Du; Xun-le Zhang; Wen-fu Chen (Journal of Mountain Science, 2023)

Derivation of copper water quality criteria in Bohai Bay for the protection of local aquatic life and the ecological risk assessment - Yang Li; Di Mu; Hong-Qing Wu; Hai-Jiao Liu; Yong-Hui Wang; Guo-Chen Ma; Xue-Min Duan; Jian-Jun Zhou; Chun-Ming Zhang; Xing-Hua Lu; Xian-Hua Liu; Jun Sun; et al. (Marine Pollution Bulletin, 2023)

Investigation on the formation mechanism of main products from TBBPA pyrolysis using DFT method - Xin Mu; Yao Wang; Jinbao Huang; Lin Lan; Hong Wang; Weiwei Xu; Xinsheng Li (Chemosphere, 2023)

Dough rheological properties, texture, and structure of high-moisture starch hydrogels with different potassium-, and calcium-based compounds - Hong-Yuan Zhang; Hong-Nan Sun; Meng-Mei Ma; Tai-Hua Mu (Food Hydrocolloids, 2023)

Production, identification and characterization of antioxidant peptides from potato protein by energy-divergent and gathered ultrasound assisted enzymatic hydrolysis - Hui Liu; Hong-Nan Sun; Miao Zhang; Tai-Hua Mu; Nasir Mehmood Khan (Food Chemistry, 2023)

Coupling coordination relationships between air pollutant concentrations and emissions in China - Qian Wu; Song Hong; Lu Yang; Hang Mu; Chaoqing Huang; Xiaoxiao Niu; Yanmei Zhong; Jiahui Yi; Chao He (Atmospheric Pollution Research, 2023)

Modification of anaerobic digestion model No.1 with Machine learning models towards applicable and accurate simulation of biomass anaerobic digestion - Yadong Ge; Junyu Tao; Zhi Wang; Chao Chen; Lan Mu; Haihua Ruan; Yakelin Rodríguez Yon; Hong Su; Beibei Yan; Guanyi Chen (Chemical Engineering Journal, 2023)

Ozone exposure and health risks of different age structures in major urban agglomerations in People’s Republic of China from 2013 to 2018 - Lu Yang; Song Hong; Hang Mu; Jingwei Zhou; Chao He; Qian Wu; Xi Gong (Environmental Science and Pollution Research, 2023)

Theoretical study on pyrolysis mechanism of decabromodiphenyl ether (BDE-209) using DFT method - Yao Wang; Jinbao Huang; Hong Wang; Lin Lan; Xin Mu; Weiwei Xu; Shanjin Lv; Xinsheng Li (Chemosphere, 2023)

Formation mechanisms and atmospheric implications of summertime nitrous acid (HONO) during clean, ozone pollution and double high-level PM2.5 and O3 pollution periods in Beijing - Huiying Xuan; Yaqi Zhao; Qingxin Ma; Tianzeng Chen; Jun Liu; Yonghong Wang; Chang Liu; Yafei Wang; Yongchun Liu; Yujing Mu; Hong He (Science of The Total Environment, 2023)

Biogenetic peloidal micrites within coral skeletons cause geochemical anomalies in reef limestones, Zhongsha Atoll, South China Sea - Hong-Qiang Yang; Xi-Yang Zhang; Yue Li; Qi Shi; Shi-Chen Tao; Xi-Nan Mu; Ming-Zhuang Wang; Xiao-Ju Liu; Fei Tan; Sheng-Nan Zhou; Guan Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

High-efficient and recoverable Mo72V30@Fe3O4/C catalyst for oxidation of hydroxyfurfural - Mengdi Gong; Xin-Yu Wang; Mu-Qin Li; Wen-Xia Mu; Yun-Dong Cao; Hong Liu; Yu-Guang Lv; Xin-Hua Qi; Guang-Gang Gao (Fuel, 2023)

Simulations of nitrous oxide emissions and global warming potential in a C4 turfgrass system using process-based models - Mu Hong; Yao Zhang; Ross C. Braun; Dale J. Bremer (European Journal of Agronomy, 2023)

Graphene induced structure and doping level tuning of evaporated CsPbBr3 on different substrates - Zhaorui Wen; Yunlei Zhong; Bingchen He; Gang Wang; Shengwen Li; Zhen Mu; Jielei Li; Junpeng Xie; Yi Zheng; Guichuan Xing; Guo Hong; Shi Chen (Chemical Engineering Journal, 2023)

Body mass index–based predictions and personalized clinical strategies for colorectal cancer in the context of PPPM - Yun-Jia Gu; Li-Ming Chen; Mu-En Gu; Hong-Xiao Xu; Jing Li; Lu-Yi Wu (EPMA Journal, 2022)
Currently colorectal cancer (CRC) is the third most prevalent cancer worldwide. Body mass index (BMI) is frequently used in CRC screening and risk assessment to quantitatively evaluate weight. However, the impact of BMI on clinical strategies for CRC has received little attention. Within the framework of the predictive, preventive, and personalized medicine (3PM/PPPM), we hypothesized that BMI stratification would affect the primary, secondary, and tertiary care options for CRC and we conducted a critical evidence-based review. BMI dynamically influences CRC outcomes, which helps avoiding adverse treatment effects. The outcome of surgical and radiation treatment is adversely affected by overweight (BMI ≥ 30) or underweight (BMI < 20). A number of interventions, such as enhanced recovery after surgery and robotic surgery, can be applied to CRC at all levels of BMI. BMI-controlling modalities such as exercise, diet control, nutritional therapy, and medications may be potentially beneficial for patients with CRC. Patients with overweight are advised to lose weight through diet, medication, and physical activity while patients suffering of underweight require more focus on nutrition. BMI assists patients with CRC in better managing their weight, which decreases the incidence of adverse prognostic events during treatment. BMI is accessible, noninvasive, and highly predictive of clinical outcomes in CRC. The cost–benefit of the PPPM paradigm in developing countries can be advanced, and the clinical benefit for patients can be improved with the promotion of BMI-based clinical strategy models for CRC.

Residual analysis of QoI fungicides in multiple (six) types of aquatic organisms by UPLC-MS/MS under acutely toxic conditions - Hong Li; Shuai Hu; Fengshou Sun; Qi Sun; Ning Wang; Beixing Li; Nan Zou; Jin Lin; Wei Mu; Xiuyu Pang (Environmental Science and Pollution Research, 2022)

Xinfangfangia pollutisoli sp. nov., Isolated from Clopyralid-Contaminated Soil - Yang Mu; Jia-Yi Peng; Hui-Ping Wang; Yue Song; Hong-Mei Wang; Qing Chen; Kai Chen (Current Microbiology, 2022)

Association of cognitive impairment and reduced cortical thickness in prefrontal cortex and anterior cingulate cortex with treatment-resistant depression - Mu-Hong Chen; Wan-Chen Chang; Pei-Chi Tu; Wei-Chen Lin; Cheng-Ta Li; Wen-Sheng Huang; Ya-Mei Bai; Shih-Jen Tsai; Tung-Ping Su (Brain Imaging and Behavior, 2022)

Stability evaluation for steep bank slope with microseismic monitoring in Three Gorges Reservoir area - Qing-ming Xie; Kui Long; Zi-mu Li; Li-chuan Chen; Hong Liu; Hong Xu; Fei He; Dan Liang; Xue-kun Xiang; Qiang Ma (Journal of Mountain Science, 2022)

Tropical and subtropical Asia's valued tree species under threat - Hannes Gaisberger; Tobias Fremout; Chris J. Kettle; Barbara Vinceti; Della Kemalasari; Tania Kanchanarak; Evert Thomas; Josep M. Serra‐Diaz; Jens‐Christian Svenning; Ferry Slik; Wichan Eiadthong; Kandasamy Palanisamy; et al. (Conservation Biology, 2022)
Tree diversity in Asia's tropical and subtropical forests is central to nature‐based solutions. Species vulnerability to multiple threats, which affect provision of ecosystem services, is poorly understood. We conducted a region‐wide, spatially explicit assessment of the vulnerability of 63 socioeconomically important tree species to overexploitation, fire, overgrazing, habitat conversion, and climate change. Trees were selected for assessment from national priority lists, and selections were validated by an expert network representing 20 countries. We used Maxent suitability modeling to predict species distribution ranges, freely accessible spatial data sets to map threat exposures, and functional traits to estimate threat sensitivities. Species‐specific vulnerability maps were created as the product of exposure maps and sensitivity estimates. Based on vulnerability to current threats and climate change, we identified priority areas for conservation and restoration. Overall, 74% of the most important areas for conservation of these trees fell outside protected areas, and all species were severely threatened across an average of 47% of their native ranges. The most imminent threats were overexploitation and habitat conversion; populations were severely threatened by these factors in an average of 24% and 16% of their ranges, respectively. Our model predicted limited overall climate change impacts, although some study species were likely to lose over 15% of their habitat by 2050 due to climate change. We pinpointed specific natural areas in Borneo rain forests as hotspots for in situ conservation of forest genetic resources, more than 82% of which fell outside designated protected areas. We also identified degraded areas in Western Ghats, Indochina dry forests, and Sumatran rain forests as hotspots for restoration, where planting or assisted natural regeneration will help conserve these species, and croplands in southern India and Thailand as potentially important agroforestry options. Our results highlight the need for regionally coordinated action for effective conservation and restoration.

Revising the species diversity of Hygrophorus section Olivaceoumbrini s.l. (Hygrophoraceae, Agaricales) in China - Hong-Yan Huang; Wen-Hao Zhang; Ting Huang; Shuai Jiang; Yan-Jia Hao; Man Mu; Li-Ping Tang (Mycological Progress, 2022)

Estimation and Analysis of JONSWAP Spectrum Parameter Using Observed Data around Korean Coast - Uk-Jae Lee; Weon-Mu Jeong; Hong-Yeon Cho (Journal of Marine Science and Engineering, 2022)
The relationship between significant wave height (H1/3) and period (T1/3) was obtained using wave data from the East and Yellow coasts of the Korean Peninsula to facilitate the calculations of the wave parameters. In addition, the JONSWAP spectral parameters were estimated and analyzed for all wave height ranges. The relational expression between the two wave variables (H1/3~T1/3) obtained from this study showed a significant difference from the previously proposed relational expressions, most of which tended to follow the lower limit of the data. Meanwhile, the suggested peak enhancement factor (PEF, γ) is 1–7; however, for this study, a peak control factor (PCF, γc) with a range of 0–10 was introduced. As a result of the analysis, the PCF was determined to be 1.13–1.42, which is approximately 40% smaller than the previously proposed γ = 3.3. The probability density distribution of the appropriate PCF was then calculated, and the gamma and log-normal distributions for the East and Yellow coasts of the Korean Peninsula were found, respectively. This study covered waves of all range heights, and the analysis results can be used as important data to explain the characteristics of the sea area.

Profiling of Polyphenols, Flavonoids and Anthocyanins in Potato Peel and Flesh from Four Potato Varieties - Shadrack Isaboke Makori; Tai-Hua Mu; Hong-Nan Sun (Potato Research, 2022)

Cytotoxic benzopyranone and xanthone derivatives from a coral symbiotic fungus Cladosporium halotolerans GXIMD 02502 - Chao-Nan Wang; Hu-Mu Lu; Cheng-Hai Gao; Lang Guo; Zhen-Yu Zhan; Jun-Jian Wang; Yong-Hong Liu; Song-Tao Xiang; Jian Wang; Xiao-Wei Luo (Natural Product Research, 2021)

DFT studies on pyrolysis mechanisms of tetrabromobisphenol A (TBBPA) - Jinbao Huang; Xin Mu; Xiaosong Luo; Hanxian Meng; Hong Wang; Li Jin; Xinsheng Li; Baosheng Lai (Environmental Science and Pollution Research, 2021)

A landslide in Heifangtai, northwest of the Chinese Loess Plateau: triggered factors, movement characteristics, and failure mechanism - Jia-xu Kong; Jian-qi Zhuang; Jie-wei Zhan; Zheng-wei Bai; Yan-qiu Leng; Peng-hui Ma; Jian-bing Peng; Zuo-peng Wang; Tian-feng Gu; Jia-xing Sun; Fan-chen Zhang; Yuan-jun Xu; et al. (Landslides, 2021)

Proton Pump Inhibitor Exposure and Acute Myocardial Infarction Risk: A Nested Cohort Study - Hsiang-Jung Tseng; Chih-Ming Cheng; Shih-Jen Tsai; Wei-Chen Lin; Ya-Mei Bai; Chia-Fen Tsai; Tung-Ping Su; Cheng-Ta Li; Tzeng-Ji Chen; Mu-Hong Chen (Cardiovascular Toxicology, 2021)

Polymorphisms in the DC-SIGN gene and their association with the severity of hand, foot, and mouth disease caused by enterovirus 71 - Ya-Ping Li; Mu-Qi Wang; Chen-Rui Liu; Hui-Ling Deng; Yuan Wu; Shuang-Suo Dang; Li-Hong Xu (Archives of Virology, 2021)

Interest-activity symptom severity predicts response to ketamine infusion in treatment-resistant depression - Mu-Hong Chen; Wei-Chen Lin; Hui-Ju Wu; Ya-Mei Bai; Cheng-Ta Li; Shih-Jen Tsai; Chen-Jee Hong; Pei-Chi Tu; Tung-Ping Su (Psychopharmacology, 2021)

Isolation and molecular characterization of bovine herpesvirus 4 from cattle in mainland China - Jun Lin; Rui-Hong Chen; Mu-Jiao Yang; Yuan-Mao Zhu; Fei Xue (Archives of Virology, 2021)

Quantitative Determination of Trace Lipopeptide Using HPLC through Double Carboxyls Labelling - Shi-Zhong Yang; Hong-Zhi Quan; Jin-Feng Liu; Hong-Ze Gang; Bo-Zhong Mu (International Journal of Peptide Research and Therapeutics, 2020)

Creation of fertility-restored materials for Ogura CMS in Brassica oleracea by introducing Rfo gene from Brassica napus via an allotriploid strategy - Hai-long Yu; Zhi-yuan Li; Wen-jing Ren; Feng-qing Han; Li-mei Yang; Mu Zhuang; Hong-hao Lv; Yu-mei Liu; Zhi-yuan Fang; Yang-yong Zhang (Theoretical and Applied Genetics, 2020)
Key message Ogura CMS fertility-restored materials, with 18 chromosomes, normal seed setting, stable fertility and closer genetic background to the parent Chinese kale, were successfully developed in B. oleracea via a triploid strategy for the first time. Abstract Ogura cytoplasmic male sterility (CMS) is the most widely used sterile type in seed production for commercial hybrids of Brassica oleracea vegetables. However, the natural Ogura CMS restorer line has not been found in B. oleracea crops. In this study, the triploid strategy was used with the aim to create euploid B. oleracea progenies with the Rfo gene. The allotriploid AAC hybrid YL2 was used as a male parent to backcross with Ogura CMS Chinese kale. After successive backcrosses, the BC 2 Rfo -positive individual 16CMSF2-11 and its BC 3 progenies, with 18 chromosomes, were developed, which were morphologically identical to the parent Chinese kale. Compared with F 1 and BC 1 plants, it showed stable fertility performance, and regular meiosis behavior and could produce seeds normally under natural pollination. The genomic composition analysis of Rfo -positive progenies by using molecular markers showed that more than 87% of the C-genome components of BC 3 Rfo -progenies recovered to the parent Chinese kale, while most or all of the A n -genome segments were lost in 16CMSF2-11 and its progenies. The results suggested that the genetic background of Rfo -positive individuals was closer to that of the parent Chinese kale along with backcrossing. Hereof, the Ogura CMS fertility-restored materials of Chinese kale were successfully created via triploid strategy for the first time, providing a bridge for utilizing the Ogura CMS B. oleracea germplasm in the future. Moreover, our study indicates that the triploid strategy is effective for transferring genes from B. napus into B. oleracea .

Comparison of metabolites in juice, seed and peel of sea buckthorn (Hippophae rhamnoides L. subsp. sinensis) - Chuangyun Wang; Menglin Lei; Hong Zhang; Lijuan Zhao; Zhixin Mu; Meixia Wang; Jianhua Zhang; Yan Deng; Li Zhao (Journal of Plant Biochemistry and Biotechnology, 2020)

Identification and characterization of the Bacillus atrophaeus strain J-1 as biological agent of apple ring rot disease - Yangping Mu; Ying Yue; Guirong Gu; Yiming Deng; Hong Jin; Ke Tao (Journal of Plant Diseases and Protection, 2020)

MiR-34a suppresses osteoblast differentiation through glycolysis inhibition by targeting lactate dehydrogenase-A (LDHA) - Mu Hong; Xiao-Bin Zhang; Fei Xiang; Xu Fei; Xue-Lian Ouyang; Xiao-Chun Peng (In Vitro Cellular & Developmental Biology - Animal, 2020)

Integrated assessment of the environmental and economic effects of “coal-to-gas conversion” project in rural areas of northern China - Yue Li; Xueliang Yuan; Yuzhou Tang; Qingsong Wang; Qiao Ma; Ruimin Mu; Junhua Fu; Jinglan Hong; Jon Kellett; Jian Zuo (Environmental Science and Pollution Research, 2020)

EFFECT OF A ROOT‐ZONE INJECTION IRRIGATION METHOD ON WATER PRODUCTIVITY AND APPLE PRODUCTION IN A SEMI‐ARID REGION IN NORTH‐WESTERN CHINA - Yan‐Ping Wang; Lin‐Sen Zhang; Yan Mu; Wei‐Hong Liu; Fu‐Xing Guo; Tian‐Ran Chang (Irrigation and Drainage, 2020)
Within the Chinese Loess Plateau, water resources are scarce and irrigation efficiency is a challenging issue. Traditional surface drip irrigation (SDI) methods have failed to improve irrigation efficiency and reduce surface evaporation in the region. An easy‐to‐install and practicable root‐zone injection irrigation (RII) method, with a low risk of emitter clogging and which uses subsurface infiltration‐promoting apparatuses (SIPA) to deliver water directly to the root zone, was designed and tested in an apple orchard over 3 years in northern Shaanxi, China. In the 0–0.6 m soil layer (where the apple roots are concentrated), the RII method produced consistently higher soil water content than the SDI method over all three growing seasons. The soil water content was consistently higher than 60% of field capacity, thus meeting the water requirements of fruit‐bearing apple trees. In addition, the RII method alleviated soil desiccation, significantly increased apple yields and improved fruit quality compared with the SDI method using the same volume of irrigation water. Both irrigation efficiency and water‐use efficiency were improved with the RII method. These results provide a theoretical basis for the utilization of the RII irrigation method in apple orchards in semi‐arid regions, which may improve water conservation and the sustainability of apple production. © 2019 John Wiley & Sons, Ltd.

Nonlinear optimal moisture perturbations as excitation of primary MJO events in a hybrid coupled climate model - Yuntao Wei; Hong-Li Ren; Mu Mu; Joshua-Xiouhua Fu (Climate Dynamics, 2020)
Although the moisture feedback has been well known to be essential in the Madden–Julian Oscillation (MJO) dynamics, whether its pre-moistening effect plays a key role in exciting the onset of primary MJO events, as has been confirmed in the successive initiation, remains elusive. In this study, using a hybrid coupled climate model that has a good fidelity in simulating the intraseasonal variability, we develop a new framework of methodology to investigate the nonlinear excitation of primary MJO event, of which the key achievement is the successful implementation of the conditional nonlinear optimal perturbation (CNOP). In an application of this new framework, the CNOP-type moisture perturbations are calculated for the pre-chosen non-MJO reference states and generally favor a moistening in the equatorial region while drying in the poleward. Comparisons of the model simulation with observation give credibility to the existence of moisture signals several weeks before some primary MJO events. A suite of numerical experiments confirms that the CNOPs of moisture can contribute to the excitation and propagation of strong primary MJO events while random perturbations cannot. The moisture budget analysis further reveals the central importance of the horizontal moisture advection, especially the nonlinearly upscaled moisture transports associated with the high-frequency disturbances on the quasi-3–4-day and 6–8-day synoptic time scales, in supporting the nonlinear excitation of the primary MJO events. The subgrid-scale processes of evaporation, condensation and eddy transport of moisture are found to be critical for the pre-moistening effect in the boundary layer as well. This study directly supports the vital importance of the moisture perturbations, which are characterized by a particular pattern concentrated at low levels, to the nonlinear growth and propagation of the primary MJO events.

Environmental and economic impact assessment of the alumina–carbon refractory production in China - Yuzhou Tang; Yifei Shi; Yue Li; Xueliang Yuan; Ruimin Mu; Qingsong Wang; Qiao Ma; Jinglan Hong; Shensong Cao; Jian Zuo; Jon Kellett (Clean Technologies and Environmental Policy, 2019)

Isolation and synthesis of a new benzylated alkamide from the roots of Lepidium meyenii - Yan-Qing Ye; Zu-Hong Ma; Qiao-Fen Yang; Yan-Qi Sun; Rui-Qi Zhang; Run-Fang Wu; Xin Ren; Li-Juan Mu; Zhi-Yong Jiang; Min Zhou (Natural Product Research, 2019)

A Novel Application of Fluorine Doped Carbon Dots Combining Vortex-Assisted Liquid-Liquid Microextraction for Determination of 4-Nitrophenol with Spectrofluorimetric Method - Shouai Feng; Zhao Mu; Hong Liu; Jiangfeng Huang; Xiaolan Li; Yaling Yang (Journal of Fluorescence, 2019)

Geosites in Karamay city, Xinjiang Uygur Autonomous Region, northwest China - Jun-Ting Qiu; Liang Qiu; Hong-Xu Mu; Wen-Xin Yang; Feng Chen; Bo-Kun Yan; Jun-Chuan Yu; He-Ming Yang (Geoheritage, 2019)

Four new phenolic constituents from the rhizomes of Gastrodia elata Blume - Zhi-Wei Wang; Yun Li; Da-Hui Liu; Yan Mu; Hong-Jing Dong; Hong-Lei Zhou; Lan-Ping Guo; Xiao Wang (Natural Product Research, 2019)

Regulation of flowering time via miR172-mediated APETALA2-like expression in ornamental gloxinia (Sinningia speciosa) - Xiao-yan Li; Fu Guo; Sheng-yun Ma; Mu-yuan Zhu; Wei-huai Pan; Hong-wu Bian (Journal of Zhejiang University-SCIENCE B, 2019)

Pedobacter pollutisoli sp. nov., Isolated from Tetrabromobisphenol A-Contaminated Soil - Yang Mu; Zhuang Ke; Chen-Xi Feng; Xiao-Wei Wang; Xiao-Wen Wang; Hong-Mei Wang; Qing Chen; Jian He (Current Microbiology, 2019)

Tepidicella baoligensis sp. nov., A Novel Member of Betaproteobacterium Isolated from an Oil Reservoir - Jing You; Yongbin Li; Shan Hong; Jing Wang; Jiliang Yu; Bozhong Mu; Xiaochen Ma; Yanfen Xue (Current Microbiology, 2019)

Blockade of Endogenous Angiotensin-(1–7) in Hypothalamic Paraventricular Nucleus Attenuates High Salt-Induced Sympathoexcitation and Hypertension - Xiao-Jing Yu; Yu-Wang Miao; Hong-Bao Li; Qing Su; Kai-Li Liu; Li-Yan Fu; Yi-Kang Hou; Xiao-Lian Shi; Ying Li; Jian-Jun Mu; Wen-Sheng Chen; Wei Cui; et al. (Neuroscience Bulletin, 2019)

Coralloluteibacterium thermophilus sp. nov., A Gammaproteobacterium Isolated from an Oil Reservoir - Jing You; Shan Hong; Jiliang Yu; Lisha Duan; Bo Liu; Bozhong Mu; Cheng Zhou; Yanfen Xue (Current Microbiology, 2018)

Focusing one-stationary bistatic forward-looking synthetic aperture radar based on squint minimization and modified nonlinear chirp scaling algorithm - Mu Liang; Weimin Su; Chao Ma; Hong Gu; Jianchao Yang (International Journal of Remote Sensing, 2018)

Association of TRIMCyp and TRIM5α from assam macaques leads to a functional trade-off between HIV-1 and N-MLV inhibition - Dan Mu; Jia-Wu Zhu; Feng-Liang Liu; Hong-Yi Zheng; Yong-Tang Zheng (Science China Life Sciences, 2018)

Long non-coding RNA (lncRNA) MAGI2-AS3 inhibits breast cancer cell growth by targeting the Fas/FasL signalling pathway - Yong Yang; Hong Yang; Miao Xu; Haibin Zhang; Mingtao Sun; Peng Mu; Tongbao Dong; Shanmei Du; Kui Liu (Human Cell, 2018)

The levels of polycyclic aromatic hydrocarbons (PAHs) in human milk and exposure risk to breastfed infants in petrochemical industrialized Lanzhou Valley, Northwest China - Li Wang; Aiping Liu; Yuan Zhao; Xi Mu; Tao Huang; Hong Gao; Jianmin Ma (Environmental Science and Pollution Research, 2018)

Planetary scale selection of the Madden–Julian Oscillation in an air-sea coupled dynamic moisture model - Yuntao Wei; Fei Liu; Mu Mu; Hong-Li Ren (Climate Dynamics, 2018)

Characteristics of thawed interlayer and its effect on embankment settlement along the Qinghai-Tibet Railway in permafrost regions - Zhi-zhong Sun; Wei Ma; Shu-juan Zhang; Yan-hu Mu; Han-bo Yun; Hong-lei Wang (Journal of Mountain Science, 2018)

Microsatellite DNA analysis reveals lower than expected genetic diversity in the threatened leopard cat (Prionailurus bengalensis) in South Korea - Byung June Ko; Junghwa An; Hong Seomun; Mu-Yeong Lee; Soo Hyung Eo (Genes & Genomics, 2018)

Effect of cultivar and growing medium on the fruit quality attributes and antioxidant properties of tomato (Solanum lycopersicum L.) - Shimeles Tilahun; Mu Hong Seo; Do Su Park; Cheon Soon Jeong (Horticulture, Environment, and Biotechnology, 2018)

Anomalous gray matter structural networks in recent onset post-traumatic stress disorder - Shun Qi; Yun-Feng Mu; Long-Biao Cui; Jian Zhang; Fan Guo; Qing-Rong Tan; Mei Shi; Kang Liu; Yi-Bin Xi; Nan-Yin Zhang; Xiao-Liang Zhang; Yong He; et al. (Brain Imaging and Behavior, 2018)

Accuracy evaluation of the crop-weather yield predictive models of Italian ryegrass and forage rye using cross-validation - Jing-Lun Peng; Moon-Ju Kim; Mu-Hwan Jo; Doo-Hong Min; Kyung-Dae Kim; Bae-Hun Lee; Byong-Wan Kim; Kyung-Il Sung (Journal of Crop Science and Biotechnology, 2017)

Enlightenments from researches and predictions of 2014–2016 super El Niño event - Mu Mu; Hong-Li Ren (Science China Earth Sciences, 2017)

Recessive male sterility in cabbage (Brassica oleracea var. capitata) caused by loss of function of BoCYP704B1 due to the insertion of a LTR-retrotransposon - Jia-lei Ji; Li-mei Yang; Zhi-yuan Fang; Mu Zhuang; Yang-yong Zhang; Hong-hao Lv; Yu-mei Liu; Zhan-sheng Li (Theoretical and Applied Genetics, 2017)

The spatial distribution of threats to plant species with extremely small populations - Chunjing Wang; Jing Zhang; Jizhong Wan; Hong Qu; Xianyun Mu; Zhixiang Zhang (Frontiers of Earth Science, 2017)

Morphological and molecular characterization of the second backcross progenies of Ogu-CMS Chinese kale and rapeseed - Hai-long Yu; Zhi-yuan Li; Li-mei Yang; Yu-mei Liu; Mu Zhuang; Lu-gang Zhang; Hong-hao Lv; Zhan-sheng Li; Feng-qing Han; Xiao-ping Liu; Zhi-yuan Fang; Yang-yong Zhang (Euphytica, 2017)

NOX2 Mediated-Parvalbumin Interneuron Loss Might Contribute to Anxiety-Like and Enhanced Fear Learning Behavior in a Rat Model of Post-Traumatic Stress Disorder - Fang-fang Liu; Lin-dong Yang; Xiao-ru Sun; Hui Zhang; Wei Pan; Xing-ming Wang; Jian-jun Yang; Mu-huo Ji; Hong-mei Yuan (Molecular Neurobiology, 2016)

Reactive Oxygen Species-mediated Loss of Phenotype of Parvalbumin Interneurons Contributes to Long-term Cognitive Impairments After Repeated Neonatal Ketamine Exposures - Hui Zhang; Xiao-ru Sun; Jing Wang; Zhen-zhen Zhang; Hong-ting Zhao; Hui-hui Li; Mu-huo Ji; Kuan-yu Li; Jian-jun Yang (Neurotoxicity Research, 2016)

Effects of light curing modes and ethanol-wet bonding on dentin bonding properties - Mu-zi Li; Jin-rui Wang; Hong Liu; Xia Wang; Kang Gan; Xiu-ju Liu; De-li Niu; Xiao-qing Song (Journal of Zhejiang University-SCIENCE B, 2016)

Rational Improvement of Peptide Affinity to Human Pregnancy-Related Serine Protease HtrA3 PDZ Domain by Introducing a Halogen Bond to the Domain–Peptide Complex Interface - Hong Liu; Shuo-Fen Dou; Xue Zhang; Yan Wang; Qing-Li Wen; Ya-Nan Mu (International Journal of Peptide Research and Therapeutics, 2016)

A graphical model for haloanhydrite components and P-wave velocity: A case study of haloanhydrites in Amu Darya Basin - Tong-Cui Guo; Hong-Jun Wang; Long-Xin Mu; Xing-Yang Zhang; Zhi Ma; Yu Tian; Hao-Chen Li (Applied Geophysics, 2016)

Development of a novel allele-specific Rfo marker and creation of Ogura CMS fertility-restored interspecific hybrids in Brassica oleracea - Hai-long Yu; Zhi-yuan Fang; Yu-mei Liu; Li-mei Yang; Mu Zhuang; Hong-hao Lv; Zhan-sheng Li; Feng-qing Han; Xiao-ping Liu; Yang-yong Zhang (Theoretical and Applied Genetics, 2016)

Methylenebisnicotiflorin: a rare methylene-bridged bisflavonoid glycoside from ripe Pu-er tea - Mu-Ke Tao; Min Xu; Han Zhang; Hui Chen; Chang Liu; Hong-Tao Zhu; Dong Wang; Chong-Ren Yang; Ying-Jun Zhang (Natural Product Research, 2016)

Association of Optic Radiation Integrity with Cortical Thickness in Children with Anisometropic Amblyopia - Shun Qi; Yun-Feng Mu; Long-Biao Cui; Rong Li; Mei Shi; Ying Liu; Jun-Qing Xu; Jian Zhang; Jian Yang; Hong Yin (Neuroscience Bulletin, 2016)

IL-1α-induced microvascular endothelial cells promote neutrophil killing by increasing MMP-9 concentration and lysozyme activity - Xiaoye Liu; Hong Dong; Mingming Wang; Ying Gao; Tao Zhang; Ge Hu; Huiqing Duan; Xiang Mu (Immunologic Research, 2016)

Molecular characterization of Beclin 1 in rare minnow (Gobiocypris rarus) and its expression after waterborne cadmium exposure - Xiao-Hong Liu; Zhi-Jian Wang; Dong-Ming Chen; Mu-Fei Chen; Xing-Xing Jin; Jing Huang; Yao-Guang Zhang (Fish Physiology and Biochemistry, 2016)

Meiofauna distribution in intertidal sandy beaches along China shoreline (18°–40°N) - Er Hua; Zhinan Zhang; Hong Zhou; Fanghong Mu; Jia Li; Ting Zhang; Bingqing Cong; Xiaoshou Liu (Journal of Ocean University of China, 2016)

Degradation of p-Nitrophenol in Soil by Dielectric Barrier Discharge Plasma - Rui Li; Yanan Liu; Yu Sun; Wenjuan Zhang; Ruiwen Mu; Xiang Li; Hong Chen; Pin Gao; Gang Xue; Stephanie Ognier (Water, Air, & Soil Pollution, 2015)

Bone Tissue Engineering by Using Calcium Phosphate Glass Scaffolds and the Avidin–Biotin Binding System - Min-Chul Kim; Min-Ho Hong; Byung-Hyun Lee; Heon-Jin Choi; Yeong-Mu Ko; Yong-Keun Lee (Annals of Biomedical Engineering, 2015)

Trend of blood lead, mercury, and cadmium levels in Korean population: data analysis of the Korea National Health and Nutrition Examination Survey - Jeong-Wook Seo; Byoung-Gwon Kim; Yu-Mi Kim; Rock-Bum Kim; Jin-Yong Chung; Kyoung-Mu Lee; Young-Seoub Hong (Environmental Monitoring and Assessment, 2015)

Detection of inherited mutations for hereditary cancer using target enrichment and next generation sequencing - Yanfang Guan; Hong Hu; Yin Peng; Yuhua Gong; Yuting Yi; Libin Shao; Tengfei Liu; Gairui Li; Rongjiao Wang; Pingping Dai; Yves-Jean Bignon; Zhe Xiao; et al. (Familial Cancer, 2015)

LNA-modified isothermal oligonucleotide microarray for differentiating bacilli of similar origin - Jing Yan; Ying Yuan; Runqing Mu; Hong Shang; Yifu Guan (Journal of Biosciences, 2014)

Breeding of cabbage (Brassica oleracea L. var. capitata) with fusarium wilt resistance based on microspore culture and marker-assisted selection - Hong-hao Lv; Qing-biao Wang; Li-mei Yang; Zhi-yuan Fang; Yu-mei Liu; Mu Zhuang; Yang-yong Zhang; Yu-hong Yang; Bing-yan Xie; Xiao-wu Wang (Euphytica, 2014)

Transcriptome sequencing and analysis of sweet osmanthus (Osmanthus fragrans Lour.) - Hong Na Mu; Huo Gen Li; Liang Gui Wang; Xiu Lian Yang; Tao Ze Sun; Chen Xu (Genes & Genomics, 2014)

The Association of RAB18 Gene Polymorphism (rs3765133) with Cerebellar Volume in Healthy Adults - Chih-Ya Cheng; Albert C. Yang; Chu-Chung Huang; Mu-En Liu; Ying-Jay Liou; Jaw-Ching Wu; Shih-Jen Tsai; Ching-Po Lin; Chen-Jee Hong (The Cerebellum, 2014)

Therapeutic radionuclides in nuclear medicine: current and future prospects - Chai-Hong Yeong; Mu-hua Cheng; Kwan-Hoong Ng (Journal of Zhejiang University-SCIENCE B, 2014)

The Protective Effect of a Metallic Selenopeptide with Superoxide Dismutase and Glutathione Peroxidase Activities Against Alcohol Induced Injury in Hepatic L02 Cells - Wang Cheng; Shen Na; Yan Gang-lin; Sui Chun-hong; Zhuang Jian-jian; Lü Shao-wu; Luo Gui-min; Mu Ying (International Journal of Peptide Research and Therapeutics, 2014)

Cycloartane-type triterpene glycosides from Beesia calthaefolia and their anticomplement activity - Li-Hua Mu; Hong-Jie Li; Dai-Hong Guo; Jin-Yuan Zhao; Ping Liu (Journal of Natural Medicines, 2014)

Effect of the BDNF Val66Met Polymorphism on Regional Gray Matter Volumes and Cognitive Function in the Chinese Population - Mu-En Liu; Chu-Chung Huang; Mu-Hong Chen; Albert C. Yang; Pei-Chi Tu; Heng-Liang Yeh; Chen-Jee Hong; Jin-Fan Chen; Jen-Ping Hwang; Ching-Po Lin; Shih-Jen Tsai (NeuroMolecular Medicine, 2014)

Interleukin-1 beta C-511T polymorphism modulates functional connectivity of anterior midcingulate cortex in non-demented elderly Han males - Pei-Chi Tu; Tung-Ping Su; Chu-Chung Huang; Albert C. Yang; Heng-Liang Yeh; Chen-Jee Hong; Ying-Jay Liou; Mu-En Liu; Ching-Po Lin; Shih-Jen Tsai (Brain Structure and Function, 2014)

New cycloartane triterpene glycosides from Beesia calthaefolia - Hong-Jie Li; Li-Hua Mu; Xian-Zhe Dong; Xiao-Yue Ge; Ping Liu (Natural Product Research, 2013)

Cytokine Profile of a Self-Healing Fonsecaea pedrosoi Infection in Murine Model - Hong Wang; Weidong Mu; Qing Ja; Miao Zhang; Ruie Chen; Guixia Lv; Yongnian Shen; Weida Liu (Cell Biochemistry and Biophysics, 2013)

Synthesis, physico-chemical properties, and antimicrobial evaluation of a new series of iron(III) hexadentate chelators - Yuan-Yuan Xie; Mu-Song Liu; Pan-Pan Hu; Xiao-Le Kong; Di-Hong Qiu; Ji-Lin Xu; Robert C. Hider; Tao Zhou (Medicinal Chemistry Research, 2013)

Repeat oral dose toxicity studies of melamine in rats and monkeys - Richard J. Early; Hong Yu; Xueyan Peter Mu; Haiyan Xu; Lei Guo; Qingxue Kong; Junma Zhou; Bruce He; Xiuying Yang; Hailiang Huang; Edward Hu; Ying Jiang (Archives of Toxicology, 2013)

Erratum to: UDP-glucuronosyltransferase 1A1 is the principal enzyme responsible for puerarin metabolism in human liver microsomes - Cheng-Feng Luo; Bin Cai; Ning Hou; Mu Yuan; Shi-Ming Liu; Hong Ji; Long-Gen Xiong; Wei Xiong; Jian-Dong Luo; Min-Sheng Chen (Archives of Toxicology, 2012)

UDP-glucuronosyltransferase 1A1 is the principal enzyme responsible for puerarin metabolism in human liver microsomes - Cheng-Feng Luo; Bin Cai; Ning Hou; Mu Yuan; Shi-Ming Liu; Hong Ji; Long-Gen Xiong; Wei Xiong; Jian-Dong Luo; Min-Sheng Chen (Archives of Toxicology, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Clinical significance of peritumoral lymphatic vessel density and lymphatic vessel invasion detected by D2-40 immunostaining in FIGO Ib1-IIa squamous cell cervical cancer - Ying Xiong; Li-Ping Cao; Hui-Lan Rao; Mu-Yan Cai; Li-Zhi Liang; Ji-Hong Liu (Cell and Tissue Research, 2012)

Mechanistic insights into the link between visfatin gene C-1535T polymorphism and coronary artery disease: an in vitro study - Yong-Sheng Wang; Wei Gao; Hong-Fen Li; Ze-Mu Wang; Jun Zhu; Huan Zhao; Jian-Jun Yan; En-Zhi Jia; Zhi-Jian Yang; Lian-Sheng Wang (Molecular and Cellular Biochemistry, 2012)

Sucrose treatment alters floral induction and development in vitro in gloxinia - Ming-Zhe Zhang; Li-Ling Wang; Dan Ye; Xi Chen; Zhi-Yi Wu; Xiao-Jia Lin; Wu-Jian Chen; Hong-Wu Bian; Ning Han; Mu-Yuan Zhu (In Vitro Cellular & Developmental Biology - Plant, 2012)

Optimisation of preparation conditions and properties of phytosterol liposome-encapsulating nattokinase - Xu-Yan Dong; Fan-Pi Kong; Gang-You Yuan; Fang Wei; Mu-Lan Jiang; Guang-Ming Li; Zhan Wang; Yuan-Di Zhao; Hong Chen (Natural Product Research, 2012)

Large-scale sequencing of normalized full-length cDNA library of soybean seed at different developmental stages and analysis of the gene expression profiles based on ESTs - Ai-Hua Sha; Chen Li; Xiao-Hong Yan; Zhi-Hui Shan; Xin-An Zhou; Mu-Lan Jiang; Han Mao; Bo Chen; Xia Wan; Wen-Hui Wei (Molecular Biology Reports, 2012)

Quantitative analysis of multiple gene promoter methylation in Korean non-small cell lung cancer patients and its association study with cancer risk factor and survival - Ho-Jin Kang; En-Jung Kim; Kyoung-Mu Lee; Mee-Sook Roh; Jong-Young Kwak; Sang-Yong Lee; Gi-Young Huh; Young-Seoub Hong (Molecular & Cellular Toxicology, 2012)

The 18p11.22 locus is associated with never smoker non-small cell lung cancer susceptibility in Korean populations - Myung-Ju Ahn; Hong-Hee Won; Jeeyun Lee; Seung-Tae Lee; Jong-Mu Sun; Yeon Hee Park; Jin Seok Ahn; O Jung Kwon; Hojoong Kim; Young Mog Shim; Jhingook Kim; Kwhanmien Kim; et al. (Human Genetics, 2012)

Activation of glycine site and GluN2B subunit of NMDA receptors is necessary for ERK/CREB signaling cascade in rostral anterior cingulate cortex in rats: Implications for affective pain - Hong Cao; Wen-Hua Ren; Mu-Ye Zhu; Zhi-Qi Zhao; Yu-Qiu Zhang (Neuroscience Bulletin, 2012)

Degenerate primer design to clone the human repertoire of immunoglobulin heavy chain variable regions - Ying Sun; Hong-Yan Liu; Ling Mu; En-Jie Luo (World Journal of Microbiology and Biotechnology, 2012)

Regulation of auxin response by miR393-targeted transport inhibitor response protein 1 is involved in normal development in Arabidopsis - Zhe-Hao Chen; Mao-Lin Bao; Yu-Zhe Sun; Yan-Jun Yang; Xiao-Hong Xu; Jun-Hui Wang; Ning Han; Hong-Wu Bian; Mu-Yuan Zhu (Plant Molecular Biology, 2011)

Functional analysis of a rice late pollen-abundant UDP-glucose pyrophosphorylase (OsUgp2) promoter - Ziying Huang; Zhaosheng Gan; Yongsheng He; Yiheng Li; Xiangdong Liu; Hong Mu (Molecular Biology Reports, 2011)

The genetic profiling of preferentially expressed genes in murine splenic CD8α+ dendritic cells - Tao Li; Wu-Ying Li; Hui-Ling Bai; Hong-Bing Ma; Hu Zhang; Jiang-Mu Zhu; Xiao-Hong Li; Hong-Ying Huang; Yuan-Fang Ma; Xin-Ying Ji (Immunologic Research, 2011)

No Association of Angiotensin I Converting Enzyme I/D Polymorphism with Domain-Specific Cognitive Function in Aged Men without Dementia - Mu-En Liu; Shih-Jen Tsai; Ti Lu; Cheng-Jee Hong; Ming-Chao Chen; Shoa-Lin Lin; Heng-Liang Yeh; Yan-Chiou Ku (NeuroMolecular Medicine, 2011)

Genetic polymorphism analysis of 15 STR loci in Chinese Hui ethnic group residing in Qinghai province of China - Ya-jun Deng; Bo-feng Zhu; Chun-mei Shen; Hong-dan Wang; Jing-feng Huang; Yuan-zhe Li; Hai-xia Qin; Hao-fang Mu; Jie Su; Jie Wu; Bo Zhang; Shuan-liang Fan (Molecular Biology Reports, 2011)

The effects of lazaroid U-74389G in a rat sepsis model - Yun-Te Chang; Shue-Ren Wann; Kai-Hseng Hsieh; Yung-Ching Liu; Ching-Hsiung Chang; Mu-Shun Huang; Chun-I Huang; Hong-Tai Chang (Inflammation Research, 2011)

Efficiency of methods applied for goat estrous synchronization in subtropical monsoonal climate zone of Southwest China - Yongju Zhao; Jiahua Zhang; Hong Wei; Xinming Sun; Biao Mu; Mingju Yu; Lingbing Wang (Tropical Animal Health and Production, 2010)

The effective expression of xylanase gene in Candida utilis by 18S rDNA targeted homologous recombination in pGLR9K - Wang Wei; Yang Hong-Lan; Bao HuiFang; Zhang Daoyuan; Shan Qi-mu-ge; Andrew J. Wood (Molecular Biology Reports, 2010)

Immune response to fused core protein of hepatitis C virus and truncated tetanus toxin peptides in mice - Xing-bin Hu; Qiao-hong Yue; Hai-feng Ouyang; Yao-zhen Chen; Xue-qing Xu; Wen Yin; San-hua Wei; Xian-qing Zhang; Shi-jie Mu (Archives of Virology, 2010)

Molecular characterization and association analysis of porcine PANE1 gene - Honggang Huang; Hong Deng; Yiling Yang; Zhonglin Tang; Shulin Yang; Yulian Mu; Wentao Cui; Jing Yuan; Zhenfang Wu; Kui Li (Molecular Biology Reports, 2010)

Copper affects biofilm inductiveness to larval settlement of the serpulid polychaete Hydroides elegans (Haswell) - Wei-Yang Bao; On-On Lee; Hong-Chun Chung; Mu Li; Pei-Yuan Qian (Biofouling, 2010)

Identification and characterization of two Bamboo (Phyllostachys praecox) AP1/SQUA-like MADS-box genes during floral transition - Er-Pei Lin; Hua-Zheng Peng; Qun-Ying Jin; Min-Juan Deng; Tao Li; Xin-Chao Xiao; Xi-Qi Hua; Kui-Hong Wang; Hong-Wu Bian; Ning Han; Mu-Yuan Zhu (Planta, 2009)

Overexpression of the cucumber LEAFY homolog CFL and hormone treatments alter flower development in gloxinia (Sinningia speciosa) - Ming-Zhe Zhang; Dan Ye; Li-Lin Wang; Ji-Liang Pang; Yu-Hong Zhang; Ke Zheng; Hong-Wu Bian; Ning Han; Jian-Wei Pan; Jun-Hui Wang; Mu-Yuan Zhu (Plant Molecular Biology, 2008)

Sulfotransferase 1A1 and glutathione S-transferase P1 genetic polymorphisms modulate the levels of urinary 8-hydroxy-2′-deoxyguanosine in betel quid chewers - Ruey-Hong Wong; Chiung-Wen Hu; Ching-Ying Yeh; Mu-Rong Chao; Chin-Chun Chen; Jun-Huang Huang; Shih-Hsien Chang; Shin-I Lee; Hong-Shen Lee (Archives of Toxicology, 2008)

Molecular cloning and characterisation of a non-TIR-NBS-LRR type disease resistance gene analogue from sugarcane - Q. You-Xiong; L. Jian-Wei; Z. Ji-Sen; R. Miao-Hong; X. Li-Ping; Z. Mu-Qing (Sugar Tech, 2008)

Antifungal agent and other constituents from Cynanchum otophyllum - Yi-Bin Zhao; Yue-Mao Shen; Hong-Ping He; Quan-Zhang Mu; Xiao-Jiang Hao (Natural Product Research, 2007)

Pharmacokinetic study with N-Ile1-Thr2-63-desulfato-r-hirudin in rabbits by means of bioassay - Guo-zhu Han; Hong-can Ren; Yong Lu; Ying Li; Shu Xiao; Hong-wei Ye; He-mu Wang (Journal of Zhejiang University-SCIENCE B, 2006)

Production of transgenic creeping bentgrass Agrostis stolonifera var. palustris plants by Agrobacterium tumefaciens-mediated transformation using hygromycin selection - Ning Han; Dong Chen; Hong-Wu Bian; Min-Juan Deng; Mu-Yuan Zhu (Plant Cell, Tissue and Organ Culture (PCTOC), 2005)

Use of oligonucleotide fingerprinting and faecal DNA in identifying the distribution of the Chinese tiger (Panthera tigris amoyensis Hilzheimer) - Qiu-Hong Wan; Sheng-Guo Fang; Guo-Fu Chen; Zhang-Ming Wang; Ping Ding; Mu-Yuan Zhu; Kong-Shou Chen; Jiu-Hua Yu; Yue-Ping Zhao (Biodiversity and Conservation, 2003)

Temporal and spatial expression of biologically active human factor VIII in the milk of transgenic mice driven by mammary-specific bovine α-lactalbumin regulation sequences - Chuan-Mu Chen; Chih-Hong Wang; Shinn-Chih Wu; Chih-Cheng Lin; Shwu-Hwa Lin; Winston T.K. Cheng (Transgenic Research, 2002)

Progress in urban geomorphology - Jin-hong Huang; Gui-chun Mu (Chinese Geographical Science, 2000)

Identification by PCR of receptor-like protein kinases from Arabidopsis flowers - Taku Takahashi; Jing-Hong Mu; Alexander Gasch; Nam-Hai Chua (Plant Molecular Biology, 1998)

Expression of human muscarinic cholinergic receptors in tobacco - Jing-Hong Mu; Nam-Hai Chua; Elliott M. Ross (Plant Molecular Biology, 1997)